Targeting Glioma Stem Cells by Functional Inhibition of Dynamin 2: A Novel Treatment Strategy for Glioblastoma. (16th March 2019) - Luwor, Rodney; Morokoff, Andrew P.; Amiridis, Stephanie; D'Abaco, Giovanna; Paradiso, Lucia; Stylli, Stanley S.; Nguyen, Hong P. T.; Tarleton, Mark; Young, Kelly A.; O'Brien, Terence J.; Robinson, Phillip J.; Chircop, Megan; et al.
Abstract: Glioma stem cells (GSCs) play major roles in drug resistance, tumour maintenance and recurrence of glioblastoma. We investigated inhibition of the GTPase dynamin 2 as a therapy for glioblastoma. Glioma cell lines and patient-derived GSCs were treated with dynamin inhibitors, Dynole 34-2 and CyDyn 4-36. We studied about cell viability, and GSC neurosphere formation in vitro and orthotopic tumour growth in vivo . Dynamin inhibition reduced glioblastoma cell line viability and suppressed neurosphere formation and migration of GSCs. Tumour growth was reduced by CyDyn 4-36 treatment. Dynamin 2 inhibition therefore represents a novel approach for stem cell-directed Glioblastoma therapy.